Promoting Critical Thinking through Task-Based Instruction (2022)
ABSTRACT : This paper reports the process and outcomes of an action research and teaching experience attempting to promote critical thinking through Task-Based Instruction in second-grade students. The project was developed with a group of 28 students in the EFL class at a public institution in La Ceja, Antioquia, Colombia. Data gathering instruments included students’ survey, journal entries and students’ artifacts. Findings referred to students’ development of critical thinking andstudents were encouraged to become agents of change, the implementation of contextualized tasks provided positive learning experiences and fostered interaction among students, other language learning cognitive tools were developed and finally, students’ behavioral and cognitive processes improved as well.